Improved preservation of human corneal basement membrane following freezing of donor tissue for epikeratophakia. Issue 11 (November 1994) - Young, R D; Armitage, W J; Bowerman, P; Cook, S D; Easty, D L
Abstract : Current methods for the production of lenticules for epikeratophakia involve rapid freezing, cryolathing, and slow warming of the donor cornea. We have found that this procedure causes structural damage to the epithelial basement membrane in the donor cornea which may subsequently contribute to poor postoperative re-epithelialisation of the implant, leading to graft failure. Endeavouring to overcome these problems, the effects of cryoprotection of donor cornea were investigated, using dimethyl sulphoxide, in conjunction with different cooling and warming rates as part of the protocol for cryolathing. The structural integrity of the epithelial basement membrane zone (BMZ) was then assessed by electron microscopy and by immunofluorescence microscopy using antibodies to types IV and VII collagen, components of the basal lamina and anchoring fibrils respectively, and an antibody to a component of the anchoring filaments. No differences in the pattern of immunostaining for these components were detected, indicating that the composition of the BMZ was unaltered by the different treatment regimens applied. However, electron microscopy showed that preservation of basement membrane ultrastructure was markedly improved when cornea was warmed rapidly rather than slowly, both in cryoprotected and non-cryoprotected tissue. Epithelial cell retention and preservation of stromal architecture appeared superior in cryoprotected samples, while keratocyte structure was heterogeneous throughout the experimental groups. Further work is in progress to assess the efficacy of these protocols in the preservation of keratocyte viability in association with improved basement membrane structure in donor tissue for epikeratophakia.